Development of Slow Release Fertilisers for Pineapple - Mohamed Ganawa, Eltaib Saeed (1999)
A compound fertiliser was prepared using different types of straight fertilisers from urea (46% N), China phosphate rock (CPR) (32% P205), muriate of potash (60% K20), gypsum (31 % CaO), kieserite (27% MgO), and copper sulphate (32% CuO). Granualator machine was used in the preparation of granular compound fertilisers. The compound fertiliser showed high percentage of K and N, 16.3 1 and 15.05%, respectively and between 0.091 and 4. 12% for other elements. The strength of compound fertilisers was measured immediately and after 9 months of the preparation with the values correspond 3.5 and 0.5 Mpa, respectively. Four types of coating materials were used in the preparation of the slow release compound fertiliser. With the exception of poly lactic acid (PLA), the method used for coating of the compound fertiliser with polyacrylamide (PA), polyvinyl chloride (PVC), and natural rubber (NR) were similar. Differential scanning calorimetry (DSC) and thermogravimetry analysis (TGA) studies showed the thermal behavior of the coating materials, and also TGA indicated the temperature at which the degradation of coating materials may occurr. The thickness of different coating material was determined by scanmng electronmicroscope (SEM) and the thickest value was obtained using PVC (3.04 µm).